2009
DOI: 10.4049/jimmunol.182.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human Neonatal CD8+ T Cells Are Subject to Immunomodulation by Direct TLR2 or TLR5 Stimulation

Abstract: In conditions of optimal priming, the neonate possess competency to mount quantitatively adult-like responses. Vaccine formulations containing sufficiently potent adjuvants may overcome the neonates’ natural tendency for immunosuppression and provoke a similarly robust immune response. TLR expression on T cells represents the possibility of directly enhancing T cell immunity. We examined the ex vivo responsiveness of highly purified human cord blood-derived CD8+ T cells to direct TLR ligation by a repertoire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
72
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 56 publications
7
72
0
2
Order By: Relevance
“…Our initial rationale for choosing flagellin hinged on its capacity to promote a T cell response, given the known expression of TLR5 on primate T cells (67), with the hypothesis that this would support the antibody response. Further, there are data supporting the ability of flagellin to enhance the activation of T cells isolated from infants (40). Specifically, cord blood-derived CD8 ϩ T cells exhibited increased levels of proliferation and IFN-␥ production when stimulated in the presence of flagellin (40).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our initial rationale for choosing flagellin hinged on its capacity to promote a T cell response, given the known expression of TLR5 on primate T cells (67), with the hypothesis that this would support the antibody response. Further, there are data supporting the ability of flagellin to enhance the activation of T cells isolated from infants (40). Specifically, cord blood-derived CD8 ϩ T cells exhibited increased levels of proliferation and IFN-␥ production when stimulated in the presence of flagellin (40).…”
Section: Discussionmentioning
confidence: 94%
“…Further, there are data supporting the ability of flagellin to enhance the activation of T cells isolated from infants (40). Specifically, cord blood-derived CD8 ϩ T cells exhibited increased levels of proliferation and IFN-␥ production when stimulated in the presence of flagellin (40). While it has not yet been reported, if flagellin engagement by neonatal CD4 ϩ T cells has a similar effect, which seems likely, given the expression of TLR5 on CD4 ϩ T cells (68), then we would predict that flagellin could support the generation of a Th response that promotes antibody production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, when cultured with anti-CD3 with/without Pam3Cys-SK (TLR2 ligand) or LPS (TLR4 ligand), only Pam3Cys-SK increased T-cell proliferation and IFN-γ production (20). Similarly, recent studies have indicated that CD3/CD28-activated CD8+ T cells are functionally responsive to direct stimulation by TLR2 ligand Pam3CYs (38). In the absence of specific antigen, TLR2 acts as a costimulatory receptor on CD8+ T cells to directly control memory CD8+ T-cell proliferation and IFN-γ production (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that TLRs are also expressed on T lymphocytes, including CD4 ϩ , CD8 ϩ , and Foxp3 ϩ regulatory T cells. TLR2, TLR5, and TLR7-TLR8 (TLR7/8) can provide a second signal for activation of T cells upon TCR engagement (3,10,25,27,30,33). M. tuberculosis expresses several TLR ligands, including the cell membrane-associated lipoproteins LpqH (Rv3763), LprG (Rv1411c), and LprA (Rv1270c); cell wall glycolipids (TLR2); and mycobacterial DNA containing CpG motifs (TLR9) (18,19,28,37,41).…”
mentioning
confidence: 99%